ANALISIS EKUITAS MEREK LAPTOP PADA MAHASISWA INSTITUT PERTANIAN BOGOR - Sumarwan, Ujang; Retnaningsih, Retnaningsih; Fitriyana, Hanisa Rahmina (Jurnal Ilmu Keluarga dan Konsumen, 2010)
The brand has role in bridging between consumer’s expectations and company’s promises. Prestigious brand can be said that it has strong brand equity. This research had objective to analyze brand equity of laptop product among students of Bogor Agricultural University. Meanwhile, this research had detail purposes are: (1) to analyze usage behavior of laptop product, (2) to analyze brand equity elements (brand awareness, brand association, perceived quality, and brand loyalty) among students of Bogor Agricultural University, and (3) to find out the correlation between top of mind and laptop brand that used by students of Bogor Agricultural University. This research used cross sectional study design with total sample were 200 students. The determination of total samples in each faculty used proportional sampling. The process to select sample was executed by convenience sampling that was selection of the samples based on availability to fill up the questionnaire and interview that appropriated with the quota in each faculty. The brand of laptop that most used and possessed is Acer. The most possessed of laptop by sample during 10 months until 18 months. The most way of buying laptop was bought by parents in new product. On the brand awareness elements of brand product, Acer generally get the better spot then followed by Toshiba, HP Compaq, and Axioo. The testing of brand association with using Cochran test showedthat the smallest association was obtained to Acer brand. It caused the other brand, such as Toshiba, HP Compaq, and Axioo hadall associations that adhere to consumers. The perceived quality that was tested by Customer Satisfaction Index (CSI), referred that index satisfaction of samples about Acer, Toshiba, and Axioo brand had satisfied level. Meanwhile, the samples that used HP Compaq had very satisfied level. The Importance Performance Analysis (IPA) showed that only Toshiba brand that was the most excellent in which none atribute which was fixed. For brand loyalty element, HP Compaq brand had the most high loyalty of consumer than the others. The Chi Square test showed that the correlation between top of mind and laptop brand that used was consistent that indicatedtop of mind was suit with laptop brand that used.